Large joint and lower extremity involvement have higher impact on disease outcomes in oligoarticular psoriatic arthritis - (:unkn) unknown (WILEY, 2020)
Objective Joints with different sizes and anatomical locations can be affected in psoriatic arthritis (PsA). Our aim was to explore the effect of different joint patterns on patient-reported outcomes (PROs) in patients with mono-oligoarthritis. Methods Within PsArt-ID (Psoriatic Arthritis- International Database), 387/1670 patients who had mono-oligoarthritis (1-4 tender and swollen joints) were enrolled in cross-sectional assessment. The joints were categorized according to their size (small/large) and location (upper/lower extremity) and PROs, physician global assessment and C-reactive protein (CRP) were compared. Analysis was made by categorizing according to joint counts (1-2 joints/ 3-4 joints). Results The mean age (SD) was 46.9 (14.24) with a mean (SD) PsA duration of 3.93 (6.03) years. Within patients with 1-2 involved joints (n = 302), size of the joints only had an impact on CRP values with large joints having higher CRP (P = .005), similar to lower extremity involvement (P = .004). PROs were similar regardless of size or location if 1-2 joints were inflamed. Within patients with 3-4 involved joints (n = 85), patient global assessment (PGA), pain, fatigue and physician global assessment were higher in the group with large joints. Similarly, PGA, pain, and physician global assessment were higher in patients with lower extremity involvement as well as higher CRP values. Conclusion For PsA patients with 3-4 joints involved, lower extremity and large joints are associated with poorer outcomes with worse PROs, physician global assessment, and higher CRP. The size and anatomical location of the joints are less important for patients with 1-2 joints in terms of the PROs.
Keywords: oligoarthritis; patient-reported outcomes; psoriatic arthritis; CLASSIFICATION CRITERIA